The Suitability of Various Plasmin Preparations for the Functional Assay of α2-Antiplasmin in Plasma - Kluft, C; Traas, D W; Jie, A F H; Nobel, E Hoegee-de (Thrombosis and Haemostasis, 1982)
Various plasmin preparations were tested for their suitability for use in the assay of α2-antiplasmin in blood plasma by the immediate plasmin inhibition test.Activation of plasminogen, viz., 1-Glu-plasminogen and/or 77-Lys-plasminogen, by immobilized urokinase results in plasmin preparations suitable for this α2-antiplasmin test. Plasmins obtained by »spontaneous« activation procedures in glycerol containing solutions, however, appeared not to be suitable. In this second group, the behaviour of the plasmins resembles that of 442-Val-plasmin (miniplasmin), which is known to show a low inactivation rate with α2-antiplasmin due to the absence of lysine-binding sites in the plasmin molecule.Evidence is presented that, in the nonsuitable plasmins, the lysine-binding sites, although not completely absent, have at least partly lost their functional integrity.
Keywords: Fibrinolysis; Plasmin; α2-Antiplasmin; H-D-Val-Leu-Lys-pNA